2009
DOI: 10.1093/aje/kwp062
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonsteroidal Antiinflammatory Agents and Incidence of Ovarian Cancer in 2 Large Prospective Cohorts

Abstract: Epidemiologic data on the association between nonsteroidal antiinflammatory drugs (NSAIDs) and ovarian cancer risk have been inconsistent. The authors prospectively examined the association between regular use of aspirin and nonaspirin NSAIDs and ovarian cancer incidence among 197,486 participants of the Nurses' Health Study (NHS) and the Nurses' Health Study-II (NHS-II) over 24 and 16 years of follow-up, respectively. Information on aspirin was initially assessed in 1980 (NHS) and 1989 (NHS-II) and on nonaspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 50 publications
4
52
1
1
Order By: Relevance
“…Compared to women who reported no use of aspirin, the relative risks of OC for those who used aspirin < 2, 2–5 times, and ≥ 6 times per week were 0.83, 0.77, and 0.61, respectively ( P =0.04) but no association was observed between NSAID use and risk. Conversely, in the NHS I and II 338 regular use of NSAIDS was protective (HR=0.81, 95% CI: 0.64–1.01) but aspirin use was not (HR=1.11, 95% CI: 0.92–1.33). No dose-response relationship with increased frequency or duration of use was observed, and results did not differ when stratifying by tumor histology 338 .…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 91%
See 2 more Smart Citations
“…Compared to women who reported no use of aspirin, the relative risks of OC for those who used aspirin < 2, 2–5 times, and ≥ 6 times per week were 0.83, 0.77, and 0.61, respectively ( P =0.04) but no association was observed between NSAID use and risk. Conversely, in the NHS I and II 338 regular use of NSAIDS was protective (HR=0.81, 95% CI: 0.64–1.01) but aspirin use was not (HR=1.11, 95% CI: 0.92–1.33). No dose-response relationship with increased frequency or duration of use was observed, and results did not differ when stratifying by tumor histology 338 .…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 91%
“…Conversely, in the NHS I and II 338 regular use of NSAIDS was protective (HR=0.81, 95% CI: 0.64–1.01) but aspirin use was not (HR=1.11, 95% CI: 0.92–1.33). No dose-response relationship with increased frequency or duration of use was observed, and results did not differ when stratifying by tumor histology 338 . A recent pooled analysis of 12 case-control studies in the OCAC 340 found aspirin use was associated with a reduced risk of OC (OR=0.91, 95% CI: 0.84–0.99), especially among daily users of low-dose (<100 mg) aspirin (OR=0.66, 95% CI: 0.53–0.83).…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 91%
See 1 more Smart Citation
“… A: Forest plot summarizing individual effect estimates from fourteen studies contributing to pooled effect estimates for ovarian cancer risk in aspirin users [5,8,20,7,6,9,10,12,13,15,14,19,21]…”
Section: Figure Imentioning
confidence: 99%
“…These analyses did not show a significant association between the use of NSAIDs and ovarian cancer; however, relevant findings from at least five additional case-control studies [10,12,13,15,14], two cohort studies [20,21] and one clinical trial [24] have been published, with heterogeneous results.…”
Section: Introductionmentioning
confidence: 97%